Defining the ligand-dependent proximatome of the sigma 1 receptor - Zhao, Jing; Veeranan-Karmegam, Rajalakshmi; Baker, Frederick C.; Mysona, Barbara A.; Bagchi, Pritha; Liu, Yutao; Smith, Sylvia B.; Gonsalvez, Graydon B.; Bollinger, Kathryn E. (Frontiers in Cell and Developmental Biology, 2023)
Sigma 1 Receptor (S1R) is a therapeutic target for a wide spectrum of pathological conditions ranging from neurodegenerative diseases to cancer and COVID-19. S1R is ubiquitously expressed throughout the visceral organs, nervous, immune and cardiovascular systems. It is proposed to function as a ligand-dependent molecular chaperone that modulates multiple intracellular signaling pathways. The purpose of this study was to define the S1R proximatome under native conditions and upon binding to well-characterized ligands. This was accomplished by fusing the biotin ligase, Apex2, to the C terminus of S1R. Cells stably expressing S1R-Apex or a GFP-Apex control were used to map proximal proteins. Biotinylated proteins were labeled under native conditions and in a ligand dependent manner, then purified and identified using quantitative mass spectrometry. Under native conditions, S1R biotinylates over 200 novel proteins, many of which localize within the endomembrane system (ER, Golgi, secretory vesicles) and function within the secretory pathway. Under conditions of cellular exposure to either S1R agonist or antagonist, results show enrichment of proteins integral to secretion, extracellular matrix formation, and cholesterol biosynthesis. Notably, Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) displays increased binding to S1R under conditions of treatment with Haloperidol, a well-known S1R antagonist; whereas Low density lipoprotein receptor (LDLR) binds more efficiently to S1R upon treatment with (+)-Pentazocine ((+)-PTZ), a classical S1R agonist. Furthermore, we demonstrate that the that ligand bound state of S1R correlates with specific changes to the cellular secretome. Our results are consistent with the postulated role of S1R as an intracellular chaperone and further suggest important and novel functionalities related to secretion and cholesterol metabolism.